DIAGNOSTIC DIFFICULTIES OF THE ISOLATED LIVER TUBERCULOSIS - T. V. Serova; T. A. Gavrischuk; G. V. Afonina (Туберкулез и болезни лёгких)
The article describes the case of abdominal tuberculosis – isolated tuberculous lesion of liver. The diagnosis was based on computer tomography of the abdomen and retroperitoneal space with bolus amplification, histological testing of surgery specimens and positive results of diaskintest. This case proves the difficulties of abdominal tuberculosis diagnostics and it justifies the need to perform magnetic resonance tomography of the abdomen, and computer tomography of the abdomen with bolus amplification, special attention is to be paid to the patients with low-grade fever belonging to tuberculosis risk groups.